Design and implementation of HMI and SCADA applied to a didactic emulation of a packing process (2013)
This paper shows the design and implementation of a Human Machine Interface (HMI) in an industrial touch screen programmed in the Galileo® software and SCADA (Supervisory Control and Data Acquisition) computer system using software CoDeSys®, with those supervision, control and data acquisition for analog and digital sensors are made, applied to the emulation of a packaging process.The supervision and control of the signals are performed with the CANopen protocol. The developed system allows the user to interact directly with the emulation of the process, triggering elements of it in the computer remotely and locally using the touch screen. The SCADA and HMI are embedded in a CoDeSys® function that the user can use as a learning tool for automating the process emulation.